Numerical analysis of the behavior of special double-row support structure - Fang, Kai; Zhang, Zhongmiao; Liu, Xingwang; Zhang, Qianqing; Lin, Cungang (Journal of Civil Engineering and Management, 2013)
A special double-row support structure used for braced excavation was modeled numerically using finite element method. The performance of the braced excavation depends on the interaction between the two walls of the support structure. Comprehensive parametric studies were carried out to investigate the influence factors on the performance. It was ascertained that the support structure behavior was largely influenced by overlapping length of two support walls, embedment ratio of inner support wall and spacing between two support walls. Appropriate parameters should be chosen to limit wall deflection and to maintain the stability of the support structure.